A polyurethane foamed article, a method of making and use in insoles
Patent Information
- Application Number
- CN202611077337.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-20
AI Technical Summary
但该工艺仍依赖于模具内发泡,发泡后需经剖切工序方可获得所需厚度制品,剖切过程不仅产生较多边角料,造成原料浪费,且增加了生产工序与人工成本
本发明通过聚四亚甲基醚二醇与特定官能度及分子量聚醚多元醇的复配,结合强凝胶型胺类催化剂与稳泡开孔型硅油的协同作用,制得的聚氨酯发泡制品在110~160 kg/m3密度范围内兼具高开孔率与高回弹性,透气量可达60 L/min以上,落球回弹率不低于45%,压缩永久变形率低于5%,满足鞋垫对透气排汗与持久缓冲支撑的使用要求。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polyurethane foam material technology, specifically relating to a polyurethane foam product, its preparation method, and the application of the foam product in shoe insoles. Background Technology
[0002] Polyurethane materials are widely used in shoe insoles due to their excellent resilience and abrasion resistance. Current polyurethane insole production processes are mainly divided into two categories: direct molding and sheet slicing. Direct molding involves directly injecting the polyurethane composite material into a single-piece insole mold for foaming. While the process is relatively simple, the closed mold cavity surface leads to a dense skin layer forming on the material surface during foaming, resulting in poor breathability and causing stuffiness and odor during wear. Existing technologies typically introduce cell-opening agents or adjust the polyol components in the composite material formulation to promote cell rupture and connectivity. For example, Chinese patent CN110964169A discloses a direct-molding high-breathability polyurethane insole composite material, which increases the cell opening rate by adding polyether ester polyols to components A and B. However, due to the limitations imposed by the mold cavity in the direct molding process, material flow and cell growth during foaming are constrained by the mold wall, making it difficult to achieve uniform product density distribution. Under low-density conditions, it is challenging to simultaneously obtain high opening rate and high resilience. The sheet slicing process first injects a polyurethane composite material into a large-size mold to foam and form a thick sheet, which is then sliced by a slicing machine to the required thickness, and finally cut to form insoles. This process, by slicing the thick sheet in the middle, exposes the open-cell structure on the surface of the product, improving breathability compared to directly molded products. For example, Chinese patent CN110698627A discloses a high-breathability polyurethane sheet insole composite material, which uses a specific polyether polyol system to react with carbodiimide-modified MDI, resulting in sheet insoles with significantly improved breathability. However, this process still relies on in-mold foaming, and a slicing process is required after foaming to obtain the product of the required thickness. The slicing process not only generates a lot of scrap material, causing material waste, but also increases production steps and labor costs. At the same time, due to the uneven internal temperature gradient and pressure distribution during the foaming process of the thick sheet, the density and cell structure of different thickness positions of the sheet vary, and the batch stability of the insoles obtained after slicing still needs to be improved.
[0003] Therefore, how to provide a polyurethane foam product that can simultaneously achieve high air permeability and high resilience over a wide density range, and whose process is simple and has high raw material utilization, as well as its continuous preparation method, remains a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0004] The purpose of this invention is to overcome the aforementioned deficiencies of the prior art and provide a polyurethane foam product that combines high air permeability, high resilience, and good mechanical properties, with a density ranging from 110 to 160 kg / m³.3 The invention allows for control within a certain range, simultaneously meeting the requirements of insoles for breathability and resilience. Another objective of the invention is to provide a preparation method with a simple process, high raw material utilization, and suitability for continuous production. A further objective of the invention is to provide the application of the polyurethane foam product in insoles.
[0005] This invention improves upon existing technologies in two dimensions: composition formulation and continuous production process. Regarding the composition formulation, by introducing a compound system of polytetramethylene ether glycol and polyether polyols with specific functionality and molecular weight into the P component, and employing a strong gelling amine catalyst and a foam-stabilizing, open-cell silicone oil for synergistic effect, a high-open-cell structure is achieved during foaming, while maintaining sufficient cell wall strength, resulting in products with both high air permeability and high ball rebound rate. In terms of the process, this invention utilizes continuous injection foaming supported by a release film combined with online thickness control and post-curing processes. This allows the material to freely foam and rise on the open surface, with the thickness precisely controlled by a thickness control device. The resulting product is a continuous sheet without a dense surface skin and with open cells on both sides, eliminating the need for subsequent cutting processes and significantly reducing waste and labor costs.
[0006] To achieve the above objectives, the present invention adopts the following specific technical solution: In a first aspect, the present invention provides a polyurethane foam product, which is prepared by reacting component P and component I in a mass ratio of 100:45 to 65, and the density of the foam product is 110 to 160 kg / m3. The P component, by weight, comprises 35-55 parts polytetramethylene ether glycol, 30-50 parts polyether polyol with a functionality of 2-3.5 and a number-average molecular weight of 4000-7000, 1.5-3 parts ethylene glycol, 0.2-1.2 parts diethanolamine, 0.4-1.0 parts strong gel-type amine catalyst, 0.05-0.3 parts foaming-type amine catalyst, 0.4-1.0 parts foam-stabilizing open-cell silicone oil, and 0.6-1.1 parts water; Component I is a modified isocyanate prepolymer synthesized from polytetramethylene ether glycol and diphenylmethane diisocyanate (MDI), wherein the mass fraction of polytetramethylene ether glycol is 20-40 parts, the mass fraction of MDI is 60-80 parts, and the mass fraction of NCO in the prepolymer is 16%-22%.
[0007] In some embodiments, in the polyurethane foam product described above, the polyether polyol in component P is a propylene oxide homopolymer or a propylene oxide-ethylene oxide copolymer, with a primary hydroxyl content ≥60%. Polyether polyols with a higher primary hydroxyl content have higher reactivity, which is beneficial for forming a uniform cell network in a shorter time.
[0008] In some embodiments, the strong gel-type amine catalyst in the aforementioned polyurethane foam product is triethylenediamine or bis(dimethylaminoethyl) ether; the foaming amine catalyst is bis(dimethylaminoethyl) ether; and the foam-stabilizing open-cell silicone oil is a polysiloxane-polyoxyolefin copolymer. The strong gel-type catalyst promotes the rapid reaction of isocyanate with hydroxyl groups and water, quickly forming a gel skeleton; while the foam-stabilizing open-cell silicone oil, while providing a foam-stabilizing effect, reduces the surface tension of the cell walls, causing the cells to rupture and connect in the later stages of foaming. The two work synergistically to give the product a high open-cell ratio and a regular cell structure.
[0009] In some embodiments, the preparation step of component I in the above-mentioned polyurethane foam product includes: reacting polytetramethylene ether glycol with MDI at 70-85°C for 1-3 hours to obtain a prepolymer with an NCO content of 16%-22% by mass. Controlling the NCO content within the above range enables component I to have suitable viscosity and reactivity, ensuring thorough and uniform mixing with component P during injection mixing, and avoiding coarse cell formation due to excessively rapid reaction or cell collapse due to excessively slow reaction.
[0010] Secondly, the present invention also discloses a method for preparing the above-mentioned polyurethane foam product, comprising the following steps: (1) Polytetramethylene ether glycol, polyether polyol, ethylene glycol, diethanolamine, strong gel-type amine catalyst, foaming-type amine catalyst, foam-stabilizing open-cell silicone oil, and water are added to the reactor according to the specified ratio and stirred evenly at 25-50°C. The mixture is then dispensed to obtain component P. This step is carried out at room temperature or under slight heating conditions. The components are only physically mixed and no chemical reaction occurs. The operation is simple.
[0011] (2) Add polytetramethylene ether glycol to the reactor according to the formula, stir and heat to 65-85℃ for vacuum dehydration, cool down and add MDI, keep the reaction at 70-85℃ for 1-3 h, cool down and dispense to obtain component I. Introducing isocyanate in the form of prepolymer can reduce the intensity of the reaction during the final mixing and foaming, which is beneficial to the stable control of the cell structure.
[0012] (3) Component P and component I are fed into the material tank of the polyurethane injection machine at a mass ratio of 100:45-65. After being stirred by the mixing head, the mixture is continuously injected onto the surface of the release film on the production line. After the thickness is controlled by the thickness control device, the mixture is foamed and then placed in a curing device at a temperature of 25-120°C for curing, thus obtaining the polyurethane foamed product. In this step, the material freely foams and rises on the release film, forming a double-sided open-cell structure without a skin layer. The thickness control device can accurately control the thickness of the product, and the curing process further cross-links and perfects the polymer network, giving the product its final mechanical properties.
[0013] In some embodiments, the production line in step (3) of the above preparation method includes a release film unwinding device, a filling machine, a thickness fixing device, a heating device, a release film recycling device, and a post-curing device arranged in sequence. The release film unwinding and recycling device enables the recycling of the carrier, the heating device can adjust the curing temperature as needed, and the post-curing device ensures that the product is fully cured.
[0014] In some embodiments, in the preparation method described above, during the foaming process in step (3), the free foaming rise time of the material on the release film is 100-120 s, and the curing time of the curing device is 10-60 min. Controlling the foaming rise time within the above range is beneficial for the cells to grow and open fully before gelation; the curing time ensures that the product is completely cured and dimensionally stable.
[0015] In some embodiments, in the above preparation method, in step (3), the release film is peeled off from the surface of the product and recycled after foaming, and the resulting product is a continuous sheet with no skin on both the upper surface and the bonding surface and an open-cell structure. The resulting sheet can be directly used for subsequent cutting processes without cutting, thus eliminating the waste of scrap materials caused by cutting at the source.
[0016] Thirdly, the present invention also discloses the application of the above-mentioned polyurethane foam product or the polyurethane foam product prepared by the above-mentioned preparation method in the preparation of insoles, wherein the density of the insole is 120-150 kg / m³. 3 The insole has an air permeability of ≥80 L / min and a Shore C hardness of 25–40. Within this density and hardness range, the insole provides suitable softness and support while maintaining excellent breathability and sweat-wicking properties.
[0017] Compared with the prior art, the present invention has the following outstanding advantages: This invention utilizes a compound of polytetramethylene ether glycol and polyether polyols with specific functionality and molecular weight, combined with the synergistic effect of strong gel-type amine catalysts and foam-stabilizing, open-cell silicone oils, to produce polyurethane foam products with a strength of 110–160 kg / m³. 3 Within the density range, it combines high porosity and high resilience, with an air permeability of over 60 L / min, a ball rebound rate of no less than 45%, and a compression set of less than 5%, meeting the requirements of insoles for breathability, sweat wicking, and durable cushioning support.
[0018] This invention uses MDI prepolymerized with polytetramethylene ether glycol to form a prepolymer with an NCO content of 16% to 22% as component I. The resulting polyurethane foam products have good performance, and by adjusting the formula and process parameters, the density and hardness of the products can be adjusted within a certain range to meet different application requirements.
[0019] This invention employs a continuous injection foaming and online thickness curing process supported by a release film. The resulting product is a continuous sheet material without a dense surface skin and with openings on both sides. It can be directly cut and used without the need for traditional cutting processes, thereby reducing waste from scrap materials, simplifying the production process, improving raw material utilization, and making it suitable for large-scale production. Attached Figure Description
[0020] To more clearly illustrate the technical solution of the present invention, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 These are actual photographs of the polyurethane foam product of Embodiment 1 of the present invention.
[0022] Figure 2 This is a real photograph of the polyurethane foam product obtained by mold foaming in Comparative Example 6 of this invention.
[0023] Figure 3 This is a top-view photograph of the insole produced in Application Example 1 of the present invention.
[0024] Figure 4 This is a cross-sectional photograph of the insole prepared according to Example 1 of the present invention.
[0025] Figure 5 This is a photograph of the layered structure of the composite fabric insole in Application Example 2 of the present invention.
[0026] Figure 6 This is a top-view photograph of the insole produced in Application Example 2 of the present invention.
[0027] Figure 7 This is a cross-sectional photograph of the insole obtained in Application Example 2 of the present invention. Detailed Implementation
[0028] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0029] Unless otherwise specified, the experimental methods used in this invention are all conventional methods; the raw materials used are all commercially available industrial-grade products, and their specifications are as follows: Polytetramethylene Ether Glycol (PTMEG): Number average molecular weight 1000 or 2000, hydroxyl value approximately 56–112 mg KOH / g, water content ≤0.05%, commercially available industrial grade.
[0030] Polyether polyol A: Functionality 3.0, number average molecular weight approximately 6000, primary hydroxyl content ≥65%, propylene oxide-ethylene oxide copolymer, water content ≤0.05%, commercially available industrial grade.
[0031] Polyether polyol B: Functionality 2.0, number average molecular weight approximately 4000, primary hydroxyl content ≥60%, polypropylene oxide homopolymer, moisture content ≤0.05%, commercially available industrial grade.
[0032] Ethylene glycol: Industrial grade, purity ≥99%.
[0033] Diethanolamine: Industrial grade, purity ≥99%.
[0034] Strong gel-type amine catalyst: triethylenediamine solution, active ingredient content 33%, commercially available industrial grade.
[0035] Foaming amine catalyst: bis(dimethylaminoethyl) ether solution, active ingredient content 70%, commercially available industrial grade.
[0036] Foam-stabilizing, open-cell silicone oil: Commercially available industrial-grade polysiloxane-polyoxyolefin copolymer. Specifically, Evonik TEGOSTAB® B 8110, with a viscosity of 650–1000 mPa·s (25°C).
[0037] Standard foam leveler: General-purpose polysiloxane foam leveler, commercially available industrial grade. BD-2158, Baoerde.
[0038] Methylenediphenyl diisocyanate (MDI): 4,4'-MDI, NCO content 33.6%, commercially available industrial grade.
[0039] Example 1 A polyurethane foam product includes component P and component I, and its preparation method specifically includes the following steps: 1. Preparation of component P By weight, 42 parts of polytetramethylene ether glycol (molecular weight 1000), 40 parts of polyether polyol A, 2.2 parts of ethylene glycol, 0.6 parts of diethanolamine, 0.7 parts of triethylenediamine, 0.10 parts of bis(dimethylaminoethyl) ether, 0.7 parts of foam-stabilizing open-cell silicone oil, and 0.8 parts of deionized water were added to a reaction vessel and stirred at 35°C for 1.5 h until uniformly mixed. The mixture was then dispensed to obtain component P.
[0040] 2. Preparation of Component I By mass, 28 parts of polytetramethylene ether glycol (molecular weight 1000) were added to the reactor, stirred and heated to 75°C, dehydrated and degassed under vacuum for 1.5 h, then cooled to 50°C, 72 parts of MDI were added, stirred and heated to 80°C and kept at that temperature for 2 h, and the NCO mass content was measured to be 18.5%. The mixture was then cooled to below 40°C and packaged to obtain component I.
[0041] 3. Preparation of polyurethane foam products The above-mentioned components P and I were fed into the material tanks of a low-pressure polyurethane injection machine at a mass ratio of 100:52, with the material temperatures controlled at 28℃ and 30℃ respectively. The two components were then pumped to a mixing head via a metering pump and continuously injected onto the surface of a release film running at 3 m / min after high-speed mixing at 5000 r / min. The material freely foamed and rose on the release film, with a foaming and rising time of 110 s. Subsequently, it passed through an adjustable-gap roller-type thickness-fixing device to control the product thickness to 10 mm. The foamed sheet after thickness fixing was then placed in a curing device at 80℃ for 25 min. After discharge, the release film was peeled off and recycled, yielding a polyurethane foamed product sheet with no dense skin layer on both the upper and bonding surfaces, and possessing an open-cell structure.
[0042] Example 2 A polyurethane foam product includes component P and component I, and its preparation method specifically includes the following steps: 1. Preparation of component P By weight, 50 parts of polytetramethylene ether glycol (molecular weight 2000), 35 parts of polyether polyol A, 1.8 parts of ethylene glycol, 0.4 parts of diethanolamine, 0.5 parts of triethylenediamine, 0.08 parts of bis(dimethylaminoethyl) ether, 0.5 parts of foam-stabilizing open-cell silicone oil, and 0.7 parts of deionized water were added to a reaction vessel and stirred at 40°C for 1 hour until uniformly mixed. The mixture was then dispensed to obtain component P.
[0043] 2. Preparation of Component I By mass, 35 parts of polytetramethylene ether glycol (molecular weight 2000) were added to the reactor, stirred and heated to 70°C, vacuum dehydrated and degassed for 2 h, then cooled to 50°C, 65 parts of MDI were added, stirred and heated to 75°C and kept at that temperature for 2.5 h, and the NCO mass content was measured to be 16.8%. After cooling, the mixture was dispensed to obtain component I.
[0044] 3. Preparation of polyurethane foam products Component P and component I were fed into a filling machine at a mass ratio of 100:48, with both components at a temperature of 30°C. After high-speed mixing at 6000 r / min, the mixture was continuously poured onto the surface of the release film. The free foaming rise time was 100 s, and the thickness was controlled to 8 mm by a thickness control device. Subsequently, the mixture was cured in a curing device at 60°C for 40 min. The release film was then peeled off, yielding a polyurethane foam sheet with no dense skin layer on both the upper and bonding surfaces, and featuring an open-cell structure.
[0045] Example 3 A polyurethane foam product includes component P and component I, and its preparation method specifically includes the following steps: 1. Preparation of component P By weight, 38 parts of polytetramethylene ether glycol (molecular weight 1000), 45 parts of polyether polyol B, 2.8 parts of ethylene glycol, 1.0 part of diethanolamine, 0.9 parts of triethylenediamine, 0.15 parts of bis(dimethylaminoethyl) ether, 0.9 parts of foam-stabilizing and open-cell silicone oil, and 1.0 part of deionized water were added to a reaction vessel and stirred at 30°C for 2 h until uniformly mixed. The mixture was then dispensed to obtain component P.
[0046] 2. Preparation of Component I By mass, 22 parts of polytetramethylene ether glycol (molecular weight 1000) were added to the reactor, stirred and heated to 80°C, vacuum dehydrated and degassed for 1 hour, then cooled to 50°C, 78 parts of MDI were added, stirred and heated to 85°C and kept at that temperature for 1.5 hours. The NCO mass content was measured to be 21.2%. After cooling, the mixture was dispensed to obtain component I.
[0047] 3. Preparation of polyurethane foam products Component P and component I are fed into the injection machine at a mass ratio of 100:60. The material temperature is 25℃. After being mixed at a high speed of 4000 r / min, the mixture is continuously injected onto the surface of the release film. The free foaming rise time is 120 s. The thickness is controlled to 12 mm by a thickness control device. Then, it is placed in a curing device at a temperature of 100℃ for 15 min for curing. The release film is then peeled off to obtain a polyurethane foam sheet with no dense skin layer on the upper surface and the bonding surface and with an open-cell structure.
[0048] Example 4 A polyurethane foam product includes component P and component I, and its preparation method specifically includes the following steps: 1. Preparation of component P By weight, 35 parts of polytetramethylene ether glycol (molecular weight 2000), 50 parts of polyether polyol A, 1.5 parts of ethylene glycol, 1.2 parts of diethanolamine, 1.0 part of triethylenediamine, 0.15 parts of bis(dimethylaminoethyl) ether, 1.0 part of foam-stabilizing open-cell silicone oil, and 1.1 parts of deionized water were added to a reaction vessel and stirred at 25°C for 2 h until uniformly mixed. The mixture was then dispensed to obtain component P.
[0049] 2. Preparation of Component I By mass, 20 parts of polytetramethylene ether glycol (molecular weight 2000) were added to the reactor, stirred and heated to 65°C, vacuum dehydrated and degassed for 2 h, cooled to 50°C and then 80 parts of MDI were added, stirred and heated to 70°C and kept at that temperature for 3 h. The NCO mass content was measured to be 22.0%. After cooling, the mixture was dispensed to obtain component I.
[0050] 3. Preparation of polyurethane foam products Component P and component I are fed into the injection machine at a mass ratio of 100:65. The material temperature is 35℃. After being mixed at a high speed of 5000 r / min, the mixture is continuously injected onto the surface of the release film. The free foaming rise time is 110 s. The thickness is controlled to 6 mm by a thickness control device. Then, it is placed in a curing device at a temperature of 120℃ for 10 min for curing. The release film is then peeled off to obtain a polyurethane foam sheet with no dense skin layer on the upper surface and the bonding surface and with an open-cell structure.
[0051] Example 5 A polyurethane foam product includes component P and component I, and its preparation method specifically includes the following steps: 1. Preparation of component P By weight, 55 parts of polytetramethylene ether glycol (molecular weight 1000), 30 parts of polyether polyol B, 3.0 parts of ethylene glycol, 0.2 parts of diethanolamine, 0.4 parts of triethylenediamine, 0.05 parts of bis(dimethylaminoethyl) ether, 0.4 parts of foam-stabilizing and open-cell silicone oil, and 0.6 parts of deionized water were added to a reaction vessel and stirred at 50°C for 1 h until uniformly mixed. The mixture was then dispensed to obtain component P.
[0052] 2. Preparation of Component I By mass, 40 parts of polytetramethylene ether glycol (molecular weight 1000) were added to the reactor, stirred and heated to 85°C, and vacuum dehydrated and degassed for 1.5 h. After cooling to 50°C, 60 parts of MDI were added, stirred and heated to 85°C and kept at that temperature for 1 h. The NCO mass content was measured to be 16.0%. After cooling, the mixture was dispensed to obtain component I.
[0053] 3. Preparation of polyurethane foam products Component P and component I were fed into a filling machine at a mass ratio of 100:45, with both components at a temperature of 22°C. After high-speed mixing at 5000 r / min, the mixture was continuously poured onto the surface of the release film, with a free foaming rise time of 110 s. The thickness was controlled to 15 mm by a thickness control device, and then the mixture was cured in a curing device at 25°C for 60 min. The release film was then peeled off, yielding a polyurethane foam sheet with no dense skin layer on both the upper and bonding surfaces, and featuring an open-cell structure.
[0054] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, polyether polyol A of equal mass is used instead of polytetramethylene ether diol in component P, while all other aspects are the same.
[0055] Preparation of component P: By weight, 82 parts of polyether polyol A, 2.2 parts of ethylene glycol, 0.6 parts of diethanolamine, 0.7 parts of triethylenediamine, 0.10 parts of bis(dimethylaminoethyl) ether, 0.7 parts of foam-stabilizing open-cell silicone oil, and 0.8 parts of deionized water were added to a reaction vessel and stirred at 35°C for 1.5 h until uniformly mixed. The mixture was then dispensed to obtain component P.
[0056] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, polyether polyol B of equal mass is used instead of polytetramethylene ether diol in component P, while all other aspects are the same.
[0057] Preparation of component P: By weight, 42 parts of polyether polyol B, 40 parts of polyether polyol A, 2.2 parts of ethylene glycol, 0.6 parts of diethanolamine, 0.7 parts of triethylenediamine, 0.10 parts of bis(dimethylaminoethyl) ether, 0.7 parts of foam-stabilizing open-cell silicone oil, and 0.8 parts of deionized water were added to a reaction vessel, mixed evenly, and dispensed to obtain component P.
[0058] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, polytetramethylene ether diol is used instead of polyether polyol A in component P, while all other aspects are the same.
[0059] Preparation of component P: By weight, 82 parts of polytetramethylene ether glycol (molecular weight 1000), 2.2 parts of ethylene glycol, 0.6 parts of diethanolamine, 0.7 parts of triethylenediamine, 0.10 parts of bis(dimethylaminoethyl) ether, 0.7 parts of foam-stabilizing open-cell silicone oil, and 0.8 parts of deionized water were added to a reaction vessel, mixed evenly, and dispensed to obtain component P.
[0060] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the P component of Comparative Example 4 uses an equal mass of conventional foam stabilizer instead of foam-stabilizing and open-cell silicone oil, while everything else is the same.
[0061] Preparation of component P: By weight, 42 parts of polytetramethylene ether glycol, 40 parts of polyether polyol A, 2.2 parts of ethylene glycol, 0.6 parts of diethanolamine, 0.7 parts of triethylenediamine, 0.10 parts of bis(dimethylaminoethyl) ether, 0.7 parts of conventional foaming agent, and 0.8 parts of deionized water were added to a reaction vessel, mixed evenly, and dispensed to obtain component P.
[0062] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the MDI in Component I of Comparative Example 5 has not been prepolymerized with polytetramethylene ether glycol, and Component I is commercially available industrial-grade MDI, while all other aspects are the same.
[0063] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that Comparative Example 6 uses a traditional mold foaming process instead of a continuous release film foaming process in the preparation of polyurethane foam products.
[0064] Preparation of polyurethane foam products: Component P and component I were fed into a low-pressure injection molding machine at a mass ratio of 100:52, mixed, and then injected into an aluminum mold with internal dimensions of 300 mm × 200 mm × 10 mm. The mold temperature was preheated to 50°C. After the mold was closed for 5 minutes, it was opened, the product was removed, and then placed in an 80°C oven for curing for 25 minutes to obtain a molded foam product with a dense skin layer on the surface.
[0065] Comparative Example 7 The difference between Comparative Example 7 and Example 1 is that the curing temperature in the preparation of polyurethane foam products in Comparative Example 7 is 130°C, while all other aspects are the same.
[0066] Comparative Example 8 The difference between Comparative Example 8 and Example 1 is that in the preparation of polyurethane foam products in Comparative Example 8, the mass ratio of component P to component I is 100:70, while all other aspects are the same.
[0067] Test Example 1 To verify the performance of the polyurethane foam products of the present invention, the polyurethane foam products obtained in Examples 1-5 and Comparative Examples 1-8 were subjected to the following performance tests, and the test methods are as follows: Density: The test was conducted in accordance with GB / T 6343-2009 "Determination of apparent density of foamed plastics and rubber". The sample size was 100mm×100mm×25mm, and the average value of 5 samples was taken.
[0068] Air permeability: Tested according to GB / T 24218.15-2018 "Textiles - Nonwovens - Test Methods - Part 15: Determination of Air Permeability", using a 20 cm² air permeability meter. 2 A circular test area (approximately 50.5 mm in diameter) was used, with a test pressure difference of 200 Pa. Five tests were performed, and the average value was taken.
[0069] Falling ball rebound rate: This refers to the ratio of the height a steel ball rebounds to the height it falls after impact. It quantifies the elastic recovery ability of a material; the higher the value, the better the elasticity of the material. The test was conducted according to GB / T 6670-2008 "Determination of the rebound performance of flexible foam polymer materials by falling ball method". The sample size was 100mm × 100mm × 50mm (the sample thickness was not less than 50mm, which could be achieved by stacking multiple layers of sheets to a certain thickness, ensuring uniform thickness and tight adhesion between layers). The steel ball diameter was 16mm, and the drop height was 500mm. Five tests were performed, and the average value was taken.
[0070] Compression set: This refers to the percentage of a material's original thickness that cannot be recovered after being compressed for a certain period of time under standard conditions and the external force is removed. A higher value indicates poorer resilience after being compressed, while a lower value indicates better resilience. The test was conducted according to Method A of GB / T 6669-2008 "Determination of Compression Set of Flexible Foamed Polymer Materials," with a compression rate of 50%, a temperature of 70℃, a time of 22 hours, and a recovery time of 30 minutes. The test was performed three times, and the average value was taken.
[0071] Shore C hardness: The test was conducted using a Shore C hardness tester. The sample thickness was not less than 6 mm. The test was performed 3 times and the average value was taken.
[0072] I. Analysis of the Influence of Different Formulation Systems on the Performance of Polyurethane Foamed Products The polyurethane foam products prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 were selected for performance testing to analyze the effect of polyol in component P on the performance of polyurethane foam products.
[0073] Table 1. Performance Test Results of Polyurethane Foamed Products with Different Polyols As shown in Table 1, the polyurethane foam product prepared in Example 1 has better air permeability, drop ball rebound rate, and compression set rate than Comparative Examples 1-3. Specifically, in Comparative Examples 1 and 2, the P component was replaced with polyether polyol A and polyether polyol B, respectively, to replace polytetramethylene ether glycol. The air permeability of the resulting polyurethane foam products was much lower than that of Example 1. This is because Comparative Example 1 increased the content of polyether polyol A. Although it has high functionality and a hardness of 28, it lacks PTMEG-induced cell opening and cannot form microphase separation. The foam is sticky and has a large hysteresis loss. In addition, polyether polyol A has a high molecular weight and fewer hard segments, resulting in poor resilience. Although Comparative Example 2 uses polyether polyol B with low functionality and low crosslinking density, the cell walls are softer and easier to break. The cell opening and elasticity are better than those of Comparative Example 1, but still not as good as Example 1. This is because it lacks the strong phase separation induction effect of polytetramethylene ether glycol. At the same time, the lower crosslinking density also makes the molecular chains easy to slip during compression, resulting in lower elasticity.
[0074] Furthermore, in Comparative Example 3, the P component did not contain polyols and the amount of polytetramethylene ether glycol was increased. However, the air permeability of the resulting polyurethane foam was still lower than that of Example 1. This is because although polytetramethylene ether glycol has regular chain segments and strong crystallinity, resulting in fast gelation, strong phase separation, and good open-cell properties during foaming, excessive polytetramethylene ether glycol leads to excessively strong phase separation. This increases the viscosity of the system, restricting further flow and tearing of the cell walls. Simultaneously, the cell walls solidify prematurely, becoming brittle and prone to cracking, resulting in… The narrow micropores result in poor air permeability and elasticity, and the lack of polyols to provide toughness further reduces elasticity. Therefore, although the air permeability and drop ball rebound rate of Comparative Example 3 are better than those of Comparative Example 1 because of the superior elasticity of polytetramethylene ether glycol, the elasticity is also poor due to the excessive plastic deformation of polytetramethylene ether glycol. This proves that the P component, which is a compound of PTMEG and polyol, can only produce polyurethane foam products with good air permeability, drop ball rebound rate and compression set rate when it works synergistically within a certain dosage range.
[0075] II. Performance tests were conducted on polyurethane foam products from Examples 1, 3, and 4 to analyze the effects of foam-stabilizing open-cell silicone oil and conventional foam leveling agents on the performance of polyurethane foam products.
[0076] Table 2. Test results of the effects of different foaming agents on the product performance. As shown in Table 2, the air permeability, ball rebound rate and compression set of the polyurethane foam products prepared in Examples 1 and 3 are better than those in Comparative Example 4, indicating that the use of foam-stabilizing and open-cell silicone oil in component P is more beneficial to improving the air permeability of the product than conventional foam stabilizers.
[0077] Test Example 2 The Influence of Component I Prepolymer Design on Product Performance The polyurethane foam products of Examples 1, 2, and 5 were selected for performance testing to examine the differences between using PTMEG-modified prepolymer in component I and using pure MDI directly.
[0078] Table 3. Results of the Influence of Component Type on the Performance of Polyurethane Foamed Products As shown in Table 3, the air permeability of Examples 1 and 2 is 85 L / min and 78 L / min, respectively; while the air permeability of Comparative Example 5, which uses MDI directly without modification, is 47 L / min. Furthermore, the compression set of Comparative Example 5 is higher than that of Examples 1 and 2, indicating that using PTMEG-modified MDI prepolymer as component I results in a product with better air permeability and compression resistance.
[0079] Test Example 3 Influence of preparation process on the properties of polyurethane foam products The polyurethane foam products of Examples 1, 6, 7, and 8 were selected for performance testing to investigate the effects of continuous release film foaming process, curing temperature, and P / I ratio on performance.
[0080] Table 4. Results of the Influence of Process Conditions on the Properties of Polyurethane Foamed Products As shown in Table 4, the polyurethane foam product prepared by the continuous release film foaming process in Example 1 has an air permeability of 85 L / min, while the polyurethane foam product prepared by the mold foaming process in Comparative Example 6 has an air permeability of only 12 L / min. Furthermore, the polyurethane foam product prepared by changing the curing temperature to 130℃ in Comparative Example 7 has a lower air permeability than that of Example 1. The polyurethane foam product prepared by changing the P / I ratio to 100:70 in Comparative Example 8 has higher density and hardness, but poorer air permeability, resilience, and compression set. This indicates that the preparation process of the present invention only produces polyurethane foam products with good air permeability, resilience, and compression set under certain conditions.
[0081] Application Example 1 Single-layer breathable insole Polyurethane foam sheet (10 mm thick, 128 kg / m³) prepared according to Example 1 3 The insole is cut directly according to its design shape and trimmed to obtain a single-layer breathable insole.
[0082] The insole consists of a single foam layer with a uniform open-cell structure along its thickness, and both the upper and lower surfaces are open-cell surfaces without a leather layer. When worn, foot pressure causes the foam cells to elastically deform, creating a "pump" effect—gas is expelled from the foam cells when the insole is compressed, and fresh air is drawn in when the pressure is released, thereby accelerating the exchange of gases inside and outside the shoe cavity and keeping the feet dry.
[0083] Application Example 2 Composite fabric breathable insole Polyurethane foam sheet (8 mm thick, 135 kg / m³) prepared according to Example 2 3 It is made of a base layer and a breathable fabric layer on top.
[0084] The production steps are as follows: (1) Cut the polyurethane foam product sheet into the required insole shape to obtain the foam base layer; (2) Select breathable knitted mesh fabric or antibacterial fabric as the surface layer, with a surface layer thickness of 0.8 to 1.2 mm; (3) Spray hot melt adhesive evenly on the surface of the foamed base layer, flatten and adhere the surface layer, and then press it for 15-30 seconds at 80-100℃ and 0.1-0.3 MPa using a hot press. After cooling, the composite fabric breathable insole is obtained.
[0085] The resulting insole consists of two parts: a breathable upper layer and a polyurethane foam base layer. The upper layer provides a soft touch and moisture-wicking properties, while the foam base layer provides support, cushioning, and overall breathability. Because the foam base layer has a double-sided open-pore structure, the pores are not sealed after the upper layer is bonded together, allowing air to freely circulate through the gaps between the upper layer fibers and the pores of the foam base layer, maintaining good overall breathability. Testing showed that the insole has an air permeability of 72 L / min, a Shore C hardness of 35, and a ball rebound rate of 50%.
Claims
1. A polyurethane foam product, characterized in that, The foamed product is prepared by reacting component P and component I at a mass ratio of 100:45-65, and has a density of 110-160 kg / m³. 3 ; The P component, by weight, comprises 35-55 parts polytetramethylene ether glycol, 30-50 parts polyether polyol with a functionality of 2-3.5 and a number-average molecular weight of 4000-7000, 1.5-3 parts ethylene glycol, 0.2-1.2 parts diethanolamine, 0.4-1.0 parts strong gel-type amine catalyst, 0.05-0.3 parts foaming-type amine catalyst, 0.4-1.0 parts foam-stabilizing open-cell silicone oil, and 0.6-1.1 parts water; Component I is a modified isocyanate prepolymer synthesized from polytetramethylene ether glycol and diphenylmethane diisocyanate (MDI), wherein the mass fraction of polytetramethylene ether glycol is 20-40 parts and the mass fraction of MDI is 60-80 parts.
2. The polyurethane foam product according to claim 1, characterized in that, The polyether polyol in component P is a propylene oxide homopolymer or a propylene oxide-ethylene oxide copolymer, with a primary hydroxyl content ≥60%.
3. The polyurethane foam product according to claim 1, characterized in that, The strong gel-type amine catalyst is triethylenediamine; the foaming-type amine catalyst is bis(dimethylaminoethyl) ether; and the foam-stabilizing open-cell silicone oil is a polysiloxane-polyoxyolefin copolymer.
4. The polyurethane foam product according to claim 1, characterized in that, The NCO content of component I is 16% to 22% by mass, and the preparation steps include: reacting polytetramethylene ether glycol with MDI at 70 to 85°C for 1 to 3 hours.
5. The polyurethane foam product according to claim 1, characterized in that, The foamed product has an open cell ratio of ≥85%, an air permeability of ≥60 L / min, a drop ball rebound rate of ≥45%, and a compression set of ≤5%.
6. The method for preparing a polyurethane foam article according to any one of claims 1 to 5, characterized in that, Includes the following steps: (1) Polytetramethylene ether glycol, polyether polyol, ethylene glycol, diethanolamine, strong gel-type amine catalyst, foaming amine catalyst, foam-stabilizing open-cell silicone oil and water are added to the reactor and stirred evenly at 25-50°C to obtain component P. (2) Add polytetramethylene ether glycol to the reactor according to the ratio, stir and heat to 65-85℃ for vacuum dehydration, cool down and add MDI, keep the reaction at 70-85℃ for 1-3 h, cool down and dispense to obtain component I; (3) The P component and the I component are fed to the material tank of the polyurethane injection machine at a mass ratio of 100:45 to 65. After being stirred by the mixing head, they are continuously injected onto the surface of the release film on the production line. After the thickness is controlled by the thickness control device, the foaming is carried out. Then, it is placed in a curing device at a temperature of 25 to 120°C for curing to obtain the polyurethane foam product.
7. The preparation method according to claim 6, characterized in that, The production line in step (3) includes a release film unwinding device, a filling machine, a thickness fixing device, a heating device, a release film recycling device, and a post-curing device arranged in sequence.
8. The preparation method according to claim 6, characterized in that, In step (3), during the foaming process, the free foaming and rising time of the material on the release film is 100-120 s, and the curing time of the curing device is 10-60 min.
9. The preparation method according to claim 6, characterized in that, In step (3), the release film is peeled off from the surface of the product and recycled after foaming, and the resulting product is a continuous sheet with no skin on the upper surface and the bonding surface and an open structure.
10. The application of the polyurethane foam product according to any one of claims 1 to 5 or the polyurethane foam product prepared by the preparation method according to claims 6 to 9 in the preparation of shoe insoles, characterized in that, The density of the insole is 120-150 kg / m³. 3 Air permeability ≥80 L / min, Shore C hardness 25~40.
Citation Information
Patent Citations
High-permeability polyurethane sheet insole combined material and preparation method thereof
CN110698627A
Directly-formed high-air-permeability polyurethane insole composite material and preparation method thereof
CN110964169A